SIMPLEKS DAN MULTIPLEKS PRE-ENRICHMENT-PCR UNTUK DETEKSI Salmonella Enteritidis DAN Typhimurium PADA KARKAS AYAM - Siti Nurjanah; Winiati P. Rahayu; Ratih Dewanti-Hariyadi; Ni Gusti Ayu Made Widyatari Asthiti; Rahadina Praba Melati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2021)
A PCR assay has been developed and applied to detect Salmonella contamination in chicken carcasses. However, a concentration fewer than 3 cells per gram lead to false-negative results due to difficulties in the DNA extraction. The objective of this study was to evaluate of the influence of pre-enrichment on the sensitivity of simplex and multiplex PCR methods the detection of for Salmonella spp., S. Enteritidis and S. Typhimurium in chicken carcasses. Artificial contamination was done using very low number of Salmonella Hadar, S. Enteritidis dan S. Typhimurium and pre-enrichment was carried out by 8 hours incubation in non-selective (BPW) medium. The results showed that simplex PCR could detect Salmonella spp., S. Enteritidis and S. Typhimurium at initial numbers of 2.3, 0.9 and 2.3 MPN/mL of cells in broth medium, respectively. A multiplex PCR could detect mixed culture of the three Salmonella serovars at an initial number of 0.73 MPN/mL of cells. When compared to non-enrichment treatment, simplex pre-enrichment-PCR gave an increase in the percentage of positive results in chicken carcasses (n= 12), from 75 to 100% for Salmonella spp., from 8 to 58% for S. Typhimurium, and from 58 to 75% for S. Enteritidis. Increasing in the positive percentage was also occurred at multiplex pre-enrichment-PCR, however the concentration of S. Enteritidis primer was not optimum for detection. Pre-enrichment step significantly increases the sensitivity of PCR-based assay for detection Salmonella.